Medieval Bestiaries : New Approaches - Strickland, Debra Higgs, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
What could the phoenix, elephant, and spider teach medieval people, and what can they teach us now about human - animal relationships? Medieval Bestiaries: New Approaches offers innovative insights on questions previously unasked about a most popular type of illuminated manuscript, whose animal pictures and stories continue to entertain and inspire. Bringing together an impressive range of multi-disciplinary expertise, the authors provide fresh perspectives on previously unpublished or under-explored bestiary texts, images, methods of production, cross-literary influences, and moralized messaging. Most significantly, they move bestiaries out of their specialized scholarly corner into the wider world of animal-thinking across Christian, Jewish, and Islamic cultures, and stake a claim for animals as a central meeting-ground for medieval and modern sensibilities. Contributors are Emma Campbell, Marc M. Epstein, Erica Fudge, Larisa Grollemond, Rebecca Hill, Elizabeth Morrison, Julie Orlemanski, Alexandra Paddock, and Debra Higgs Strickland.